Moment Redistribution of Shear-Critical GFRP Reinforced Continuously Supported Slender Beams - Hazem Shebl; Amr El-Nemr (Civil Engineering Journal, 2021)
Fiber-Reinforced Concrete (FRC) is a competitive solution for the durability of reinforced structures. This paper aims to observe moment redistribution behavior occurring due to flexural and shear loading in GFRP reinforced continuous concrete beams. A rectangular cross-section was adopted in this study with dimensions of 200 mm in width and 300 mm in depth with a constant shear span-to-depth ratio of 3. The reinforcement ratio for the top and bottom were equal at sagging and hogging moment regions. A finite element model was created using ANSYS and validated with the existing experimental results in the literature review. Based on the literature review, the parametric study was conducted on twelve beam specimens to evaluate the influence of concrete compressive strength, transversal GFRP stirrups ratio, and longitudinal reinforcement ratio on the redistribution of the moment in beams. Several codes and guidelines adopted different analytical models. The CSA S806 adopted the modified compression field theory in predicting the shear capacity of the simply supported beams. Recently, various researchers encountered several factors and modifications to account for concrete contribution, longitudinal and transverse reinforcement. A comparison between the predicting shear capacity of the generated finite element model and the analytical model and the existing data from literature was held. The generated finite element model showed a good agreement with experimental results while the beam specimens failed in shear after undergoing significant moment redistribution from hogging to sagging moment region. Doi: 10.28991/CEJ-SP2021-07-02 Full Text: PDF